2011
DOI: 10.1007/s00167-011-1568-z
|View full text |Cite
|
Sign up to set email alerts
|

Tibial rotation in single- and double-bundle ACL reconstruction: a kinematic 3-D in vivo analysis

Abstract: Both "anatomic" single- and double-bundle ACL reconstruction adequately restore tibial rotational excursion in a human, "in vivo" kinematic model. As knee stability measurements by in vivo kinematic 3-D analysis more accurately represent actual knee loading during activities, the results of this study might better correlate with functional outcome after ACL reconstructions compared with static knee stability tests or ex vivo laboratory experiments. In such, the results of this dynamic study do not support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…Several recent in vivo studies using dynamic, functional activities (ie, jumping and cutting) [13,18,26] demonstrated rotational kinematics after DB ACL reconstruction were closer to normal than that after SB ACL reconstruction while other reports of rotational kinematics during walking, descending from a platform, and pivoting [11,34] have found no differences between SB and DB ACL reconstructions. The disparity of those results could be due largely to the varied loading conditions employed.…”
Section: Discussionmentioning
confidence: 94%
“…Several recent in vivo studies using dynamic, functional activities (ie, jumping and cutting) [13,18,26] demonstrated rotational kinematics after DB ACL reconstruction were closer to normal than that after SB ACL reconstruction while other reports of rotational kinematics during walking, descending from a platform, and pivoting [11,34] have found no differences between SB and DB ACL reconstructions. The disparity of those results could be due largely to the varied loading conditions employed.…”
Section: Discussionmentioning
confidence: 94%
“…Altered lower limb kinematics during the performance of different landing tasks after ACL reconstruction are commonly reported in the literature. [14][15][16][17] However, no previous authors have reported on the kinematic profiles of female ACL-R athletes during the performance of a dynamic postural stability task such as the SEBT. Nonetheless, it is possible to suggest that the same rehabilitation principles could be applicable to both situations.…”
Section: Kinematicsmentioning
confidence: 99%
“…Studies using more challenging tasks, such as pivoting and jump landing, have also demonstrated deficits in knee-joint mechanics after ACL reconstruction. [14][15][16] The results of the aforementioned studies, although informative, are limited because the primary focus has been on kneejoint mechanics with little consideration being given to proximal structures. Delahunt et al 17 observed altered hipand knee-joint angular displacements in female ACL-R athletes who had returned to sport participation when performing a high-velocity, high-load jump-landing sportspecific task.…”
mentioning
confidence: 99%
“…Several video-motion analysis studies have found no differences in knee kinematics and rotational stability between double-bundle and single-bundle ACL-reconstructed knees during gait, high-demand pivoting activities and other dynamic movement tasks (Figure 4). [57,58,59,60] These studies concluded that both techniques were able to restore tibial rotational excursion when compared with the contralateral knees and/or with control knees from uninjured subjects. However, these studies cannot definitively address differences between single and double-bundle anatomic ACL reconstruction, due to concerns regarding the ability of surface marker based techniques for assessing small (but potentially important) differences in transverse and coronal-plane rotations or assessing shifts in tibiofemoral contact locations.…”
Section: Dynamic Knee Function: Anatomical Acl Reconstructionmentioning
confidence: 99%